2022
DOI: 10.3389/fmicb.2021.810215
|View full text |Cite
|
Sign up to set email alerts
|

Chicken-Derived Pattern Recognition Receptor chLGP2 Inhibits the Replication and Proliferation of Infectious Bronchitis Virus

Abstract: The widespread nature and economic importance of Infectious bronchitis virus (IBV) and interactions between IBV and the host immune response remain poorly understood. Understanding the mechanism of virus recognition via innate immunity can help resist IBV invasion. Retinoic acid-induced gene I-like receptor (RLRs) recognize virus RNA in virus infection, and LGP2 is a member of RLRs. According to the current studies, LGP2 exhibited certain inhibition in the virus, and there is a lack of investigation for chicke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…In addition, RIG-I is also absent in chickens, which is presumably attributable to their higher susceptibility to NDV compared with waterfowls such as ducks and geese [67,68]. Instead of RIG-I, NDV and other RNA viruses are recognized by the other two RLR family members, MDA5 and LGP2, which preserve antiviral competence in chickens [69][70][71][72][73]. The infection of the virulent genotype VIId NDV strain was accompanied by massive MDA5 expression in the oviducts of egg-laying hens and chicken bone-marrow-derived dendritic cells in the early infection stage [74,75].…”
Section: Receptors For Ndv Pampmentioning
confidence: 99%
“…In addition, RIG-I is also absent in chickens, which is presumably attributable to their higher susceptibility to NDV compared with waterfowls such as ducks and geese [67,68]. Instead of RIG-I, NDV and other RNA viruses are recognized by the other two RLR family members, MDA5 and LGP2, which preserve antiviral competence in chickens [69][70][71][72][73]. The infection of the virulent genotype VIId NDV strain was accompanied by massive MDA5 expression in the oviducts of egg-laying hens and chicken bone-marrow-derived dendritic cells in the early infection stage [74,75].…”
Section: Receptors For Ndv Pampmentioning
confidence: 99%
“…It was reported that the expression of chMDA5 and chSTING were up-regulated in IBV-infected birds, which further initiated the innate immune response [ 225 , 228 ]. chLGP2, a member of RLRs with less investigated in chicken, was reported to interact with chTRBP to dampen IBV infection [ 229 ]. The research on the innate immune response to coronavirus infection in chickens is quite limited and should be highly encouraged.…”
Section: Coronavirusmentioning
confidence: 99%
“…These induced IFN-Is transduce signals to the nucleus through a cascade of related molecules and rapidly induce the expression of hundreds of IFN-stimulated genes (ISGs) [18,19]. Due to the ability to promote viral clearance, induce tissue repair, and stimulate a prolonged adaptive immune response against viruses, IFN-I responses constitute the body's first line of defense against viral infections, including IBV [20,21]. IFN-I is regulated by the gut microbiota by acting on a variety of immune cells, including natural killer cells, macrophages, and CD 8+ T cells [5,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%